Respuesta :

[tex] \bf -\sqrt{28q}\cdot -\sqrt{99q}\implies \stackrel{\textit{recall } minus\cdot minus=plus}{\sqrt{28q}\cdot \sqrt{99q}}~~
\begin{cases}
28=2\cdot 2\cdot 7\\
\qquad 2^2\cdot 7\\
99=3\cdot 3\cdot 11\\
\qquad 3^2\cdot 11
\end{cases}
\\\\\\
\sqrt{2^2\cdot 7q}\cdot \sqrt{3^2\cdot 11q}\implies 2\sqrt{7q}\cdot 3\sqrt{11q}\implies 6\sqrt{7q\cdot 11q}
\\\\\\
6\sqrt{77q^2}\implies 6q\sqrt{77} [/tex]

Below are the steps and answer to this problem


Ver imagen deadspawn
Ver imagen deadspawn